The Importance of Optimizing the Potikelek Terminal Function for the Existence of Street Vendors in Jayawijaya Regency - Nur Aini; Tati Haryati; Fortunatus Ganggut (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Transportation is a necessity for people in carrying out daily activities, in both urban and rural communities. For this reason, the Jayawijaya Regency Transportation Service is tasked with helping to optimize the function of the Potikelek terminal for the existence of street vendors, such as the comfort and security felt by the community as users. In optimizing the function of the Potikelek Terminal and the existence of street vendors. Then the various efforts made by the Regional Government. By using descriptive qualitative research methods, it is obtained that the optimization of the Potikelek Terminal function for the existence of street vendors has not been carried out properly, which is indicated by the finding that the optimization of the Potikelek Terminal function carried out by the Jayawijaya Regency Transportation Service is not optimal because there are still many obstacles. faced, such as (a) Infrastructure facilities are still far from complete; (b) People still find it difficult to use existing facilities; (c) There is still a lack of control from the government side; (d) The public is still not familiar with the signs and regulations set by the Department of Transportation; and (e) There is still a lack of coordination between the government and the community.